2013
DOI: 10.4314/jasem.v17i2.2
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Para Red Dye in Chilli Powder and Tomato Sauces by a Simple Spectrophotmetric Method followed by Thin layer Chromatography

Abstract: A number of grinded chilli powder samples and tomato sauce samples were collected from various localities of Karachi city. All the samples were estimated for the presence of para red which is an azo dye and more specifically belongs from the group of sudan dyes. According to the regulation of various governmental agencies its use in food is strictly prohibited because of its ability to form carcinogenic compounds. Although there were a number of sophisticated chromatographic methods for the estimation of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Para red was the least colourant reported to have been found in chilli pepper and tomato with an average value of 0.7 and 0.4 mg/kg, respectively. The increased presence of para red in chilli pepper than tomato was also reported by Mustafa et al [13] in estimating para red dye in chilli powder and tomato sauce. The findings in this study agree with Rao et al [22] who also reported the presence of soluble dye and rhodamine in chilli powder.…”
Section: Colourants Used To Adulterate Chilli Pepper and Tomatosupporting
confidence: 78%
See 2 more Smart Citations
“…Para red was the least colourant reported to have been found in chilli pepper and tomato with an average value of 0.7 and 0.4 mg/kg, respectively. The increased presence of para red in chilli pepper than tomato was also reported by Mustafa et al [13] in estimating para red dye in chilli powder and tomato sauce. The findings in this study agree with Rao et al [22] who also reported the presence of soluble dye and rhodamine in chilli powder.…”
Section: Colourants Used To Adulterate Chilli Pepper and Tomatosupporting
confidence: 78%
“…Dyes such as Sudan dye (I, II, III, and IV), para red dye, yellow dye (metanil yellow), and orange II, among others, have been reported to be present in condiments [13]. The use of these dyes is possibly due to their resemblance to the condiment or spices in question since they may be similar in physical or chemical structure.…”
Section: Million Tons)mentioning
confidence: 99%
See 1 more Smart Citation
“…1 An important segment is that of protein-based colorants, which have gained attention after the discovery that synthetic color compounds can cause detrimental effects on humans, like mental diseases, allergies, and cancer. 2,3 In this tenor, phycobiliproteins are a family (phycoerythrins, phycoerythrocyanins, phycocyanins and allophycocyanin) of colored proteins that have several applications, ranging from food pigmentation to molecular labeling. 4,5 These proteins form a complex in certain living organisms called phycobilisome, which helps to absorb light to perform photosynthetic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…The market of pigments, regardless of the use, has increased significantly during the past years . An important segment is that of protein‐based colorants, which have gained attention after the discovery that synthetic color compounds can cause detrimental effects on humans, like mental diseases, allergies, and cancer . In this tenor, phycobiliproteins are a family (phycoerythrins, phycoerythrocyanins, phycocyanins and allophycocyanin) of colored proteins that have several applications, ranging from food pigmentation to molecular labeling .…”
Section: Introductionmentioning
confidence: 99%